1999
DOI: 10.1017/s0958067099018060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracellular cations on the inward rectifying K+ channels Kir2.1 and Kir3.1/Kir3.4

Abstract: summaryThe effects of Ba¥, Mg¥, Ca¥ and Na¤ as blocking ions were investigated in 90 and 10 mÒ extracellular K¤ solutions on the cloned inward rectifying K¤ channel Kir2.1 expressed in Xenopus oocytes. Some data were also obtained using another inward rectifying K¤ channel Kir3.1ÏKir3.4. The addition of Ba¥ caused a concentration-, voltage-and time-dependent block of both channels. Decreasing the extracellular K¤ concentration augmented the block. The data suggest that Ba¥ blocks the channels by binding to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 4 publications
5
15
1
1
Order By: Relevance
“…Fig. 5B shows that Ba 2ϩ block of the wild-type channel was voltage-dependent and Ba 2ϩ sensitivity was greater at more negative potentials, as shown previously (21). For the wild-type channel, ␦ was 0.31 Ϯ 0.01 (n ϭ 10).…”
Section: Effect Of H5 Mutations On Slowsupporting
confidence: 82%
See 1 more Smart Citation
“…Fig. 5B shows that Ba 2ϩ block of the wild-type channel was voltage-dependent and Ba 2ϩ sensitivity was greater at more negative potentials, as shown previously (21). For the wild-type channel, ␦ was 0.31 Ϯ 0.01 (n ϭ 10).…”
Section: Effect Of H5 Mutations On Slowsupporting
confidence: 82%
“…Stock solutions of cRNA were diluted in nuclease-free water to give the appropriate concentrations prior to injection. Oocyte preparation, injection of RNA, and two-microelectrode voltage clamp recordings were performed as described previously (21). The bath solution contained (in mM): KCl 90, HEPES 5, CaCl 2 2, pH 7.4 (KOH).…”
mentioning
confidence: 99%
“…5). In addition, while GIRK (K ir 3.x) channels are also expressed within lamina I–II (Luscher et al, 1997; Marker et al, 2005; Marker et al, 2006) and highly sensitive to Ba 2+ (Owen et al, 1999; Lancaster et al, 2000), we found no evidence that these channels were constitutively active in SDH neurons at this age. This implies that differences in GIRK expression between the pacemaker and non-pacemaker populations are unlikely to explain the lower K ir conductance seen in spontaneously bursting neurons.…”
Section: Discussioncontrasting
confidence: 67%
“…It has been reported that external calcium, as well as other divalent cations, can block IRK (including K ir 3.1 and 3.4) channels (Owen et al, 1999). However there is no complete characterization of any direct inhibition of GIRK by intracellularly positioned calcium ions.…”
Section: Discussionmentioning
confidence: 99%